A Note of Dynamic Tax Incidence - Bernheim, B. Douglas (Quarterly Journal of Economics, 1981)
Under certain reasonable conditions for a growth model, the path of adjustment between steady states generated by a change in an exogenous policy variable is solved for explicitly. The overall welfare effect is then shown to be a weighted average of the short- and long-run effects for a large class of social welfare functions. These results are applied to a simple neoclassical growth model for the purpose of investigating the dynamic incidence of a labor income tax. Contrary to the claims of previous investigators, the long-run effect is shown to be more important for a wide range of parameter values.